Comparative Evaluation Of Shear Bond Strength Using “Fusion X-Tra” - A Newer Alternative Bonding Adhesive: An In-Vitro Study (Journal of Pharmaceutical Negative Results, 2022)
Objective: This in-vitro study aimed to evaluate and compare the Shear bond strength using Admira Fusion Xtra, an alternative bonding adhesive, and conventional bonding adhesive. Materials and Method: Two hundred seventy sound human maxillary premolars were randomly divided into three groups (n=90) Group 1 (Transbond XT), Group 2 (Fusion Flow), and Group 3 (Fusion Xtra) based on adhesives used for bonding the orthodontic metal brackets. All the samples were stored in artificial saliva and subjected to SBS evaluation using a universal testing machine at a cross speed of 0.5 mm2/min. The failure mode was analyzed using Adhesive Remnant Index (ARI). Statistical analysis was done using an unpaired student t-test and one-way and 3-way ANOVA for the shear bond strength and the Kruskal-Wallis test followed by Mann-Whitney was performed for ARI scores (p<0.01). Result: The mean values of shear bond strength of Admira Fusion Xtra showed statistically significant differences between other evaluated groups (p<0.001). The lowest and highest shear bond strength was attributed to each group respectively. Statistically significant differences were noted in the mean ARI scores between Fusion Xtra and another evaluated group (p<0.01). Conclusion: Admira Fusion Xtra enhances the shear bond strength of orthodontic brackets as compared to the Admira Fusion Flow and conventional orthodontic adhesive.